Comparison of Functional and Radiological Outcomes of Tears Involving the Subscapularis: Isolated Subscapularis Versus Combined Anterosuperior Rotator Cuff Tears. Issue 2 (17th February 2020) - Meshram, Prashant; Rhee, Sung-Min; Park, Joo Hyun; Oh, Joo Han
Background: Few studies have compared the clinical and radiological characteristics and outcomes in isolated subscapularis (SSC) and combined anterosuperior (AS) rotator cuff tears (RCTs). Furthermore, risk factors for retear after SSC repair and the effect of preoperative fatty degeneration require further evaluation. Purpose: To compare the functional and radiological outcomes of isolated SSC with combined AS RCTs after arthroscopic repair and to determine the risk factors for SSC retear in these 2 groups. Study Design: Cohort study; Level of evidence, 3. Methods: Data from 30 patients in the isolated SSC group were compared with data from 110 patients in the combined AS group. All patients underwent primary arthroscopic rotator cuff repair between 2010 and 2016. Clinical outcomes were assessed through use of the visual analog scale for pain, American Shoulder and Elbow Surgeons score, and Simple Shoulder Test at a mean follow-up of 26.7 months (range, 24-96 months). SSC tendon integrity was examined via magnetic resonance imaging, computed tomography arthrogram, or ultrasonography at least 1 year after surgery. Results: The isolated SSC group had a greater proportion of males and the patients were younger compared with the combined AS group (both P < .050). The incidence of trauma was high but not significantly different between groups (56.7% vs 40.9%; P = .180). Clinical outcome measures and radiological outcomes in terms of retear were not statistically different between both groups (16.7% vs 8/5%; P = .337). The optimal cutoff values for the risk of SSC tendon retear in both groups were 19-mm retraction and 16-mm superoinferior dimension ( P = .048). Unfavorable preoperative fatty degeneration of the SSC muscle (grades 3 and 4) was a significant risk factor for retear (odds ratio, 9.8; P < .001). Conclusion: Isolated SSC and combined AS RCTs were comparable except for patient age and sex; both had a high incidence of traumatic history. The current data suggest that the risk factors for retear after SSC repair in RCTs involving the SSC were tear size greater than 19 mm of retraction and unfavorable fatty degeneration (grade 3 or higher) of the SSC muscle.